BIOMECHANICAL DIFFERENCES IN LIFTERS WITH PRE-EXISTING INJURIES DURING THE SNATCH EXERCISE - DeVitto, Evan C. (East Carolina University, 2022)
Introduction: High intensity workouts are growing rapidly throughout the fitness industry. CrossFit and free weight workouts are becoming a popular standard throughout the exercise community. One of these exercises is the snatch. Weightlifting has been viewed as a high-risk sport as the rate of injury among other exercises is exponentially higher. Research has suggested that multiple repetitions can result in a breakdown in the biomechanical technique used by the lifters. This breakdown in mechanics could result in an increased risk for injuries. The purpose of this study is to quantify the biomechanical differences between lifters with pre-existing injuries and those without. We hypothesized that both sets of participants will exhibit observable breakdowns in technique, but the lifters with pre-existing injuries will show an increased loss of mechanics in body segments where they were injured previously. Methods: For this study at least 20 participants will be recruited to participate in this study. The participants in this study are between the ages of 18 and 45 years old. Participants will complete a snatch workout during a one-time visit that will last approximately 45 minutes to 1 hour. Utilizing a twelve-camera (10 infrared, 2 digital) 3D motion capture system (Opus 300+ Cameras, Qualisys, Goteborg, Sweden), kinematic data will be taken at a sampling frequency of 200 Hz in the frontal, sagittal, and transverse planes. 53 total markers will be placed onto the subject along with 6 marker plates. Once the markers are placed one static trial will be performed while the participant is holding a T-pose. Once the static trial is completed, 8 markers will be removed before the workout is completed. The weight for the workout will be based on 60% of the participant's one rep max for the snatch. The workout that participants will be completing is called, “Isabel” which consists of 30 repetitions for time. A rep count will be provided to the participant in order to maintain speed throughout the workout. The kinematic and kinetic variables of interest are 3D body segment positions and joint angles, bar height, ground reaction forces, and bar location relative to the lifter. The first repetition for each participant will be used as a baseline, and differences from the baseline for each variable will be calculated.
Keywords: Biomechanics; CrossFit; Weightlifting; Injury, Re-injury